Influence of Area Distribution Along the Span Direction on Flapping Wing Aerodynamics in Hover Based on Numerical Modeling Analysis - Guilin Wu; Shuanghou Deng; Qingxi Li (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
This study performed a numerical investigation to explore the effect of span-wise area distribution on flapping wing aerodynamics in hovering configuration using an in-house developed flow solver. The span-wise area distribution was defined using a morphological beta function and the flapping motion was set to a sinusoidal movement manner. Results show that moving the area distribution toward the tip region can generate more lift and simultaneously expense more power, whereas an optimum area distribution ( ${\rm{\bar{r}}}_1$ = 0.45) was observed because of its aerodynamic efficiency. In general, the temporal profiles of aerodynamic forces are slightly sensitive concerning span-wise area distribution rather than the peak and mean force. Detail flow structure visualization illustrated that the flapping wing locomotion produces complex spatial and temporal vortex structures, including vortex generation, development, and shedding of leading-edge vortex, trailing edge vortex, and root vortex. For flapping wing with a larger area on the tip is in principle capable of enhancing the vortex strength, particularly for the leading-edge vortex which dominates the lift generation during flapping motion. Meanwhile, the smoother profile bounded by the tip and leading edge is beneficial for stabilizing the leading edge and tip vortex.